Modelling of a PZT Beam for Voltage Generation - Nechibvute, Action; Akande, A.R; Luhanga, P.V.C (Universiti Putra Malaysia Press, 2014)
Piezoelectric materials, such as Lead Zirconate Titanate (PZT), have the ability to convert mechanical forces into an electric field in response to the application of mechanical stresses or vice versa. This novel property of the materials has found applications in sensor and actuator technologies, and recently, in the new field of energy harvesting. The study presented in this paper targets the modelling of a PZT beam device for voltage generation by transforming ambient vibrations into usable electrical energy. This device can potentially replace the battery that supplies power in microwatt range necessary for operating some wireless sensor devices. While the feasibility of this application has been repeatedly demonstrated in the literature, challenges for accurate modelling of mechanical to electrical energy generation in real world applications still remain. In this study, a simple mathematical model of simple voltage generation by a PZT beam device, based on classical beam analysis, was proposed. Experimental testing showed that the proposed model simulations are in good agreement with the experimental results. The energy harvesting capabilities of the fabricated PZT bea